Biomedical engineering concepts, methodologies, tools, and applications (Medical Information Science Reference, 2018)
"This book is an authoritative reference source for emerging scholarly research on trends, techniques, and future directions in the field of biomedical engineering technologies. Highlighting a comprehensive range of topics such as nanotechnology, biomaterials, and robotics"--Provided by publisher.